2019
DOI: 10.14814/phy2.14271
|View full text |Cite
|
Sign up to set email alerts
|

Diet‐induced obesity decreases rate‐dependent depression in the Hoffmann’s reflex in adult mice

Abstract: Obesity is associated with balance and motor control deficits. We have recently shown that Group Ia muscle spindle afferents, the sensory arm of the muscle stretch reflex, are less responsive in mice fed a high‐fat diet. Here we test the hypothesis that reflex excitability to sensory information from Group Ia muscle spindle afferents is altered in a mouse model of diet‐induced obesity. We measured the anesthetized Hoffmann’s or H‐reflex, the electrical analog of the muscle stretch reflex. Adult mice of both se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…[19,20] In contrast, altered RDD was observed in mice fed with a high-fat diet that consequently developed obesity. [21] In line with the evidence in animals, in humans, RDD impairment was reported in individuals with type-1 and type 2 diabetes with painful and non-painful neuropathy. [22,23] Recently, further exploration of optimal RDD parameters has been conducted to study spinal disinhibition in diabetic subpopulations by using stimulation frequencies <3 Hz.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…[19,20] In contrast, altered RDD was observed in mice fed with a high-fat diet that consequently developed obesity. [21] In line with the evidence in animals, in humans, RDD impairment was reported in individuals with type-1 and type 2 diabetes with painful and non-painful neuropathy. [22,23] Recently, further exploration of optimal RDD parameters has been conducted to study spinal disinhibition in diabetic subpopulations by using stimulation frequencies <3 Hz.…”
Section: Introductionsupporting
confidence: 63%
“…Previously, it was reported that diet-induced obesity in mice causes impairment of RDD. [ 21 ] Our results represent the first evidence of the loss of RDD in this population and open new questions about the consequences of overweight and obesity on sensory and motor spinal processing.…”
Section: Discussionmentioning
confidence: 76%
“…Similar conclusions were made in experiments where depression in offspring appeared on the maternal model of obesity induced by high fat diet [21]. Interestingly, one of the newer studies found that adult mice consuming a high fat diet had a lower percentage of rate dependent depression than the group of adult mice consuming the control diet [22].…”
Section: The Influence Of Diet On a Depressionmentioning
(Expert classified)
“…On the other hand, few studies have evaluated the RDD in conditions of overweight and obesity but their results are interesting. In a preclinical study ( 36 ), male and female mice were fed with a high-fat diet (HFD) and researchers measured the RDD at 5 Hz at weeks 5, 10, and 15, and observed that the HFD male group had impaired RDD at weeks 5 and 10, while the female group had impaired RDD at weeks 10 and 15, compared to the control group. However, in this study, behavioral measures of pain were not assessed to determine if worse scores were related to impaired RDD ( 36 ).…”
Section: Alterations Of the H-reflex And H-reflex Rate-dependent Depr...mentioning
confidence: 99%